Wool economy in the ancient Near East and the Aegean : from the beginnings of sheep husbandry to institutional textile industry - European Science Foundation Exploratory Workshop on Wool Economy in the Ancient Near East and the Aegean: From the Beginnings of Sheep Husbandry to Institutional Textile Industry; Breniquet, C.; Michel, Cécile (Ancient textiles series, 2014)
The history of the Ancient Near East covers a huge chronological frame, from the first pictographic texts of the late 4th millennium to the conquest of Alexander the Great in 333 BC. During these millennia, different societies developed in a changing landscape where sheep (and their wool) always played an important economic role. The 22 papers presented here explore the place of wool in the ancient economy of the region, where large-scale textile production began during the second half of the 3rd millennium. By placing emphasis on the development of multi-disciplinary methodologies, experiment
Keywords: Textile industry : Middle East : History : To 1500 : Congresses; Textile fabrics, Ancient : Middle East : Congresses; Wool : Economic aspects : Middle East : History : To 1500 : Congresses; Wool industry : Middle East : History : To 1500 : Congresses; Middle East : Antiquities : Congresses